D-cycloserine effects on COPD and depression in a murine experimental model - Heresco-Levy, Uriel; Haviv, Jacob; Caine, Yehezkel G.; Bao, Jimmy; Huang, Tai-Yu; Shen, Chien-Chang; Bogot, Naama R. (Frontiers in Pharmacology, 2025)
Background and PurposeBoth chronic obstructive pulmonary disease (COPD) and depression are associated with chronic inflammation and their comorbidity represents a critical unmet treatment need. N-methyl-D-aspartate glutamatergic receptors (NMDAR) are well characterized in CNS and widely expressed in lung tissue and inflammation-related cells. Pathologic NMDAR activation, leading to proinflammatory signaling, reactive oxidative stress and tissue damage plays a crucial role in chronic lung injury and depression. D-cycloserine (DCS), an antitubercular antibiotic, acts also as a NMDAR functional antagonist and has antidepressant and anti-inflammatory effects. We hypothesize that NMDAR downregulation represents a unified molecular target for the treatment of COPD–depression comorbidity. This study assessed whether DCS can ameliorate lung injury and depression–like behavior in the porcine pancreatic elastase (PPE)/E.coli lipopolysaccharide (LPS) murine COPD model.Material and MethodsMale BALB/c mice 7–8 weeks old received PPE intratracheally (IT) (1.2 U/20 µL/mouse) on days 0, 7, 14 and 21 and LPS (7 µg/20 µL/mouse) on days 4, 11, 18 and 25 (Groups 2–5). Sham control mice (Group 1) received same volume of saline IT in the same schedule as PPE and LPS. Vehicle (saline) or DCS 100 or 200 mg/kg were administered intraperitoneally once daily from day 28 to day 34 (Groups 2–4). An additional group (Group 5) received DCS 100 mg/kg once weekly (days 7, 14 and 21) and once daily from day 28 to day 34. On day 35 mice underwent the forced swim test (FST) and lungs were harvested for histopathological analyses.ResultsInflammatory cell infiltration, focal emphysema, measured by the mean linear intercept (MLI), and FST immobility duration, a rodent proxy for depression, were all increased (p < 0.05) in the vehicle group. In comparison with the vehicle group, immobility duration was reduced (p < 0.05) in both DCS 100 mg/kg groups. Moreover, the severity grading of lung inflammation and MLI were reduced (p < 0.05) in the DCS 100 mg/kg × 10 group and in all DCS-treated groups, respectively.ConclusionOur findings suggest beneficial DCS effects and warrant further DCS investigation as an innovative treatment for COPD-depression comorbidity.